Investing in Sustainability: How FDI and Trade Openness Affect the Consumption of Renewable Energy in Regional Comprehensive Economic Partnership (RCEP) Countries - Anika, Tasneem; Md Nazmus, Sadekin; Md.Tuhin, Ahmed; Ashiqur, Rahman; Asha, Alam; Ida, Hindarsah; Khan Sarfaraz, Ali (INTI International University, 2025)
This paper focuses on how trade openness and foreign direct investment (FDI) affect the adoption of sustainable energy among the countries of the Regional Comprehensive Economic Partnership (RCEP) based on the panel data between 1998 and 2022. The Pesaran (IPS) and Phillips-Perron tests allow to assert the stationarity of data, and the Pedroni cointegration test indicates that there is a long-term correlation between the variables, which proves the theoretical connection between economic factors and renewable energy adoption. The research employs the Pooled Ordinary Least Squares (POLS), Fully Modified Ordinary Least Squares (FMOLS) and Dynamic Ordinary Least Squares (DOLS) to estimate long-run effects and Canonical Cointegration Regression (CCR) to assure robustness. The findings indicate that FDI has a very positive and significant impact on the usage of renewable energy, which indicates that FDI promotes the transition to cleaner energy in RCEP countries. Conversely, trade openness affects the utilization of renewable energy negatively, so that increased trade may be linked to the increased utilization of fossil fuels or the trade-offs related to the environment. The results offer useful policies that would be recommended to the RCEP countries, affirming the need to attract green FDI and use sustainable trade policies and reinforce the financial mechanisms that motivate the use of renewable energy in investments. This study is an addition to the wider debate of sustainable development and energy policy because it provides a great insight of the economic factors related to the use of renewable energy in developing nations